First tungsten radiation studies in DIII-D’s ITER baseline demonstration discharges - F. Turco; T.C. Luce; ACC. Sips; C. Greenfield; T. Osborne; T. Odstrcil; J.M. Hanson; A. McLean; A.W. Hyatt (Nuclear Fusion, 2024)
ITER Baseline Scenario plasmas were studied in DIII-D using krypton and xenon gases as a proxy for the tungsten that will be present in ITER. These impurities were chosen for having the same radiative loss rate Lz as tungsten would exhibit in the hotter ITER core. Results show that the scenario with these core radiators spans the range of impurity concentration and W radiated fraction expected for ITER, and up to 50% higher values, explored at zero injected torque, as well as 1 Nm and full co-torque injection with T ∼ 3 Nm. Stationary discharges with duration >2–4 τ _R are achieved with f _rad $\unicode{x2A7E}$ 30% leading to a reduction in confinement of ∼10%, and a comparison with real metal radiators in the same range of f _rad shows that the higher Lz at the lower temperatures in these plasmas yields too pessimistic results on the survivability and performance of this scenario in ITER. Simulations of ITER power balance including W radiation show that with concentration up to three times higher than in the DIII-D plasmas the scenario can be stationary, remaining at acceptable core radiated fraction values.